Innowacje słowotwórcze we współczesnych rosyjskich mass mediach - Raciburskaja, Larysa (Studia Rossica Posnaniensia, 2010)
The article is devoted to the problem of reflection of social changes in Russia in the derivatives of mass-media. Many new word formation processes are thoroughly investigated and richly illustrated here.